2007
DOI: 10.1111/j.1526-4637.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Synera™ Patch for Local Anesthesia Before Vascular Access Procedures: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: A 20-minute application of Synera consistently provided clinically useful anesthesia for vascular access procedures, and appears to be well suited for topical dermal anesthesia due to its reduced time required to produce adequate anesthesia and high subject and investigator acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…110,111 Heat-activated systems have shortened the time required to as low as 10 to 20 minutes for IV insertion pain relief. 112 Topical anesthetics also have been reported to improve procedural success rates, likely because of decreased movement leading to better accuracy. 113,114 When the procedure cannot be delayed or needs to take place in the prehospital setting, other techniques can be used; intradermal lidocaine injection as well as intradermal saline with benzyl alcohol preservative decreases the pain of venous cannulation without affecting procedural success rate.…”
Section: Controlling Pain Related To Needle Sticks and Other Minor Prmentioning
confidence: 99%
“…110,111 Heat-activated systems have shortened the time required to as low as 10 to 20 minutes for IV insertion pain relief. 112 Topical anesthetics also have been reported to improve procedural success rates, likely because of decreased movement leading to better accuracy. 113,114 When the procedure cannot be delayed or needs to take place in the prehospital setting, other techniques can be used; intradermal lidocaine injection as well as intradermal saline with benzyl alcohol preservative decreases the pain of venous cannulation without affecting procedural success rate.…”
Section: Controlling Pain Related To Needle Sticks and Other Minor Prmentioning
confidence: 99%
“…Das Rapydan®-Pflaster (Eusa Pharma GmbH, München, Deutschland; [3,7,11]) ist ein neu entwickeltes System zur lokalen Anwendung mit 70 mg Lidocain und 70 mg Tetracain. Es enthält außerdem eine Komponente, die Wärme frei setzt (26-34°C), um die Resorption der Lokalanäs-thetika zu beschleunigen.…”
Section: Lokalanästhetikumpflasterunclassified
“…Topical anesthesia · Venous puncture · Lidocaine · Tetracaine · Pain konnte in 2 Studien eine Wirksamkeit im Vergleich zu Placebo nach einer Einwirkdauer von 20 min bei Probanden [3] bzw. Kindern [12] beobachtet werden.…”
Section: Introductionunclassified
“…Additionally, studies evaluating topical anesthetic patches have shown long time to maximum analgesic effect or increased number of side effects compared with commonly used creams or placebo application. 3,5,6 Nanotechnology is one of the promising techniques that may aid in the development of better topical anesthetic formulations. Nanocapsules are composed by a polymeric container disposed around an oily nucleus.…”
Section: Introductionmentioning
confidence: 99%